An application of Six Sigma DMAIRC model: case study of a manufacturing organisation - Sharma, Pallavi (2022)
Global competition extends several challenges to micro, small and medium enterprises (MSMEs) organisations. There is an increasing need for these firms to adopt strategies for productivity improvement. Six Sigma is a data driven methodology supported by statistical, mathematical and managerial techniques for improving the bottom line effectively. In this paper, an application of DMAIRC model of Six Sigma is presented in context to a quality improvement initiative in an MSME organisation. DMAIRC is an effective alternative to linear DMAIC model, as it provides opportunity to review results and diagnose additional improvements. The additional improvements are checked for feasibility and implemented through additional improvement cycles. The study also demonstrates integration of the quality management techniques such as Pareto analysis, cause and effect analysis, current reality tree, design of experiments, and integrated AHP-TOPSIS in the DMAIRC model stages. The paper provides a roadmap for real life applications of Six Sigma methodology following the DMAIRC model.